Pengaruh Audit Internal, Pengendalian Internal, Good Corporate Governance terhadap Pencegahan Kecurangan - Afifah, Hana (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to see how the influence of internal audit, internal control, and good corporate governance on fraud prevention at Commercial Banks in Pekanbaru City. The population in this study were employees at commercial banks in Pekanbaru City. This research uses quantitative methods. The sampling technique for this research uses purposive sampling, by distributing questionnaires as many as 100 people to bank employees who have positions as Branch Heads, Tellers, Customer Service, Marketing, and Surveyors and have work experience in positions of at least 1 year. Data processing uses quantitative methods using the SmartPLS 4 application as an analysis tool. The results in the study show that internal audit, internal control, and good corporate governance have a positive effect on fraud prevention.